The Allocation of Authority in Organizations: A Field Experiment with Bureaucrats. Issue 4 (19th August 2021) - Bandiera, Oriana; Best, Michael Carlos; Khan, Adnan Qadir; Prat, Andrea
Abstract: We design a field experiment to study how the allocation of authority between frontline procurement officers and their monitors affects performance both directly and through the response to incentives. In collaboration with the government of Punjab, Pakistan, we shift authority from monitors to procurement officers and introduce financial incentives in a sample of 600 procurement officers in 26 districts. We find that autonomy alone reduces prices by 9% without reducing quality and that the effect is stronger when the monitor tends to delay approvals for purchases until the end of the fiscal year. In contrast, the effect of performance pay is muted, except when agents face a monitor who does not delay approvals. Time use data reveal agents' responses vary along the same margin: autonomy increases the time devoted to procurement, and this leads to lower prices only when monitors cause delays. By contrast, incentives work when monitors do not cause delays. The results illustrate that organizational design and anti-corruption policies must balance agency issues at different levels of the hierarchy.